Ultrahigh-toughness multifunctional titanium alloy and preparation method thereof
By developing a super tough multifunctional titanium alloy composed of non-toxic elements, using isometric ultrafine grains and graded nanostructures, the shortcomings of existing β-Ti alloys in mechanical properties and biocompatibility are solved, and high strength and good ductility are achieved, which is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202410003871.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-08
- Filing Date
- 2024-01-02
- Publication Date
- 2025-03-11
AI Technical Summary
Existing β-Ti alloys have shortcomings in mechanical properties and biocompatibility, especially in terms of challenges in enhancing plastic behavior and improving biocompatibility.
A super tough multifunctional titanium alloy composed of non-toxic elements such as Ti, Zr, Hf, Nb and Sn was developed. Its molecular formula is TiaZrbHfcNbdSne. Its equiaxed ultrafine grain (UFG) structure and graded nanostructure are combined to achieve high strength and good ductility.
The titanium alloy exhibits a tensile strength of about 1.75 GPa and a uniform elongation of at least 20%, is able to withstand more than 1000 fatigue cycles under a constant tensile stress of 1.4 GPa, and exhibits almost complete deformation recovery between 4% and 5%.
Smart Images

Figure CN119592839A_ABST
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims priority to U.S. patent application No. 18 / 463,306 filed on September 8, 2023, the disclosure of which is incorporated herein by reference. Technical Field
[0002] The present invention generally relates to the field of material science and technology, and more specifically, provides a super-tough multifunctional titanium alloy and a preparation method thereof. Background Art
[0003] Titanium alloy is a promising material for many fields of application. Due to its high specific strength, titanium alloys such as the typical Ti-6A1-4V (TC4) have specific advantages in the aerospace and automotive industries. 1 Titanium alloys with low elastic modulus and high corrosion resistance are highly desirable biomedical materials for biological applications, such as surgical implants. 2 In recent years, biomedical titanium alloys containing non-toxic elements and showing higher biocompatibility have attracted great interest. To play the role of smart or functional materials, titanium alloys can be engineered, such as traditional Ti-Ni or metastable β-Ti alloys, to exhibit shape memory effects or pseudoelasticity. 3,4 .
[0004] In order to obtain excellent mechanical properties, the key focus of developing titanium alloys is to enhance their plastic behavior. In order to solve the problem of insufficient work hardening observed in many titanium alloys (especially TC4), alternative deformation mechanisms such as twinning or transformation induced plasticity (TWIP / TRIP) present in metastable titanium alloys have attracted great attention. 5,6 However, an increase in the work hardening rate in TRIP / TWIP alloys is usually accompanied by a decrease in the yield strength, specifically the stress level required to induce mechanical twinning or martensitic transformation. Therefore, the balance between yield strength and strain hardening remains a prominent topic of interest in recent and upcoming research works. 7 .
[0005] In the medical field, researchers are actively exploring alternatives to surgical implants made from commercial titanium alloys due to growing concerns about the presence of toxic and allergenic elements in these materials. The need for biocompatible titanium alloys has led to the development of β-Ti alloys such as Ti-Nb and Ti-Nb-Zr, which challenges the most commercially available TC4 and Ti-Ni implants, which are dangerous if corroded. 8,9 However, these β-Ti alloys have limited strength and are therefore not suitable for a variety of applications. Similar limitations exist in titanium alloys used for smart functional materials, hindering their wider application in a variety of scenarios.
[0006] Therefore, designing titanium alloys that can meet the requirements of these different applications is a complex task that requires a harmonious combination of excellent strength, biocompatibility and functional properties. Summary of the invention
[0007] Therefore, the present invention is directed to addressing the challenges associated with existing β-Ti alloys.
[0008] In a first aspect, the present invention provides a super-tough multifunctional titanium alloy made of two or more metal elements. The molecular formula of the titanium alloy is Ti a Zr b Hf c Nb d Sn e , a, b, c, d and e represent the atomic percentage of metal elements, ranging from 45≤a≤55, 36≤b≤43, 3≤c≤6, 3.5≤d≤7.5, 1.5≤e≤3. Titanium alloys present an initial microstructure characterized by an equiaxed ultrafine grain (UFG) structure, which is strengthened by a hierarchical nanostructure formed during subsequent deformation.
[0009] According to one aspect of the present invention, the titanium alloy contains 48 atomic % Ti, 39 atomic % Zr, 4.5 atomic % Hf, 6.3 atomic % Nb and 2.2 atomic % Sn.
[0010] According to one aspect of the invention, the hierarchical nanostructure comprises nanotwins, and wherein one or more nanoribbons are confined within the nanotwins.
[0011] According to one aspect of the present invention, the average size of the UFG structure is 300 nanometers to 2 micrometers.
[0012] According to one aspect of the present invention, the titanium alloy exhibits a tensile strength of about 1.75 GPa and a uniform elongation of at least 20%.
[0013] According to one aspect of the present invention, the titanium alloy is subjected to more than 1000 fatigue cycles under a constant tensile stress of 1.4 GPa.
[0014] According to one aspect of the present invention, the titanium alloy exhibits almost complete deformation recovery within a deformation range of 4% to 5%.
[0015] According to one aspect of the present invention, the titanium alloy achieves a maximum recoverable strain of about 7%.
[0016] In the second aspect, the present invention provides a method for preparing an ultra-tough multifunctional titanium alloy sheet, comprising weighing at least two raw materials with a purity higher than 95%, wherein the at least two raw materials include Ti, Zr, Hf, Nb and Sn; melting the at least two raw materials by arc melting in a pure argon atmosphere to obtain a molten alloy; casting the molten alloy into a water-cooled copper mold; cold rolling the cast alloy to reduce its thickness by 97%-99% to obtain a cold-rolled alloy sheet; wrapping the cold-rolled alloy sheet in an iron sheet, annealing at 800°C to 900°C for a period of time in a continuously flowing argon atmosphere, and then air cooling to obtain a titanium alloy sheet.
[0017] According to one aspect of the present invention, a titanium alloy containing at least two raw materials has a molecular formula Ti a ZrbHfcNbdSne, wherein a, b, c, d and e represent the atomic percentage of the metal element, ranging from 45≤a≤55, 36≤b≤43, 3≤c≤6, 3.5≤d≤7.5, 1.5≤e≤3.
[0018] According to one aspect of the present invention, the step of melting the at least two raw materials by arc melting in a pure argon atmosphere to obtain a molten alloy comprises a series of melting and remelting processes, with a total of 7-8 cycles.
[0019] According to one aspect of the present invention, the annealing time is 20 seconds to 20 minutes. When the annealing time is in the range of 25 to 45 seconds, the tensile strength of the titanium alloy is about 1.75 GPa and the uniform elongation is at least 20%. When the annealing time is in the range of 45 to 75 seconds, the titanium alloy exhibits a tensile strength of about 1.5 GPa and a uniform elongation of at least 15%. When the annealing time is in the range of 12 to 20 minutes, the titanium alloy exhibits a tensile strength of about 1.2 GPa and a uniform elongation of at least 17%.
[0020] The present invention provides a β-Ti alloy sheet composed of non-toxic elements, thereby enhancing the biocompatibility of the alloy. The alloy sheet has an equiaxed ultrafine grain (UFG) structure and is strengthened by a hierarchical nanostructure formed during deformation. The alloy is initially strengthened by its UFG structure, resulting in a first yield point of about 1.36GPa. What occurs after this first yield point is a reversible TRIP effect, which forms significant strain hardening and a large pseudo-elasticity of about 7% when unloading. Further deformation leads to the formation of nanotwins, and nanobelts are confined therein. This ongoing process continuously enhances strain hardening, ultimately resulting in an excellent tensile strength of about 1.75GPa, accompanied by a uniform elongation of at least 20%.
[0021] Compared with the prior art, the present invention has significant advantages, including: (1) The alloy’s composition consists of non-toxic elements, eliminating toxic and allergic components such as vanadium and aluminum. This feature enhances its applicability in medical applications and ensures greater safety. (2) The alloy exhibits excellent mechanical properties and also has functional characteristics. (3) Compared with other β-Ti or β+α dual-phase alloys, the current alloy exhibits significantly higher strength and highly competitive ductility due to the synergistic combination of multiple strengthening mechanisms. (4) Compared with shape memory alloys (SMA), the current alloys exhibit highly competitive pseudoelasticity, significantly higher strength and improved biocompatibility. This means that the alloys are safer in biomedical applications and are more suitable for harsh conditions such as in the aerospace or automotive industries. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The present invention will be more readily understood from the following description of exemplary embodiments with reference to the accompanying drawings, in which:
[0023] Figure 1A An inverse pole figure (IPF) image is shown, which shows the equiaxed ultrafine grain (UFG) structure of Sample 1.
[0024] Figure 1B Shown are TEM bright field images. Inset: HRTEM of [1 1 1] axis random grains.
[0025] Figure 2A An IPF image showing the equiaxed UFG structure of sample 2 is shown.
[0026] Figure 2B Shown is an IPF image at a higher magnification.
[0027] Figure 3 An IPF image is shown, which shows that the grain structure of Sample 3 is larger.
[0028] Figure 4A The engineering tensile stress-strain curve of sample 1 is shown.
[0029] Figure 4B The engineering tensile stress-strain curve of Sample 2 is shown.
[0030] Figure 4C The engineering tensile stress-strain curve of sample 3 is shown.
[0031] Figure 5 The true tensile stress-strain curve of sample 1 and the corresponding strain hardening rate are shown.
[0032] Fig. 6A The unstrained sample 1 is shown. Figure 6B Sample 1 is shown having a 10% deformation. Figure 6C Sample 1 is shown having a deformation of 15%. Fig.6D Fracture samples are shown showing nanotwins confined within ultrafine grains (UFG). Fig. 6E Demonstration of nanoribbons confined within nanotwins. Fig. 6F Shown is HRTEM at the nanoribbon interface. Figure 6G-6H exhibit Fig. 6F FFT of the region shown in , showing the non-twinned relationship between the nanoribbons.
[0033] Figure 7 Loading-unloading-reloading (LUR) curves of the tensile cycle test of Samples 1-3 are shown.
[0034] Fig. 8A The results of individual tensile tests performed at different pre-strain levels from 1% to 10% are presented.
[0035] Figures 8B-8C Shown are the LUR curves obtained from fatigue tests performed under a constant loading stress of 1.4 GPa.
[0036] Fig. 9 Shown are the potentiodynamic polarization curves of TiZrHfNbSn and TC4 alloys in simulated body fluid at 37°C. DETAILED DESCRIPTION
[0037] The present invention will also be described in detail by the following examples and accompanying drawings. It should be understood that specific embodiments are provided for illustrative purposes only and should not be interpreted in a limiting manner. Those skilled in the art will appreciate that the invention described herein may be modified and altered beyond those specifically described.
[0038] The present invention includes all such changes and modifications. The present invention also includes all steps and features mentioned or indicated in the specification individually or collectively, and any and all combinations or any two or more steps or features in the steps or features. Other aspects and advantages of the present invention will be apparent to those skilled in the art by reviewing the subsequent description.
[0039] The present invention may take advantage of the recently developed colloidal metals and Ti-Nb-Ta-Zr (TNTZ) alloys as potential candidate materials, which exhibit high yield strengths approaching 1.2 GPa and relatively low elastic moduli. The present invention may also draw inspiration from the field of metastable titanium high entropy alloys, which have functional properties derived from the reversible TRIP effect.
[0040] Therefore, the present invention provides a super-tough multifunctional titanium alloy made of two or more metal elements. The molecular formula of the titanium alloy is Ti a Zr bHf c Nb d Sn e , a, b, c, d and e represent the atomic percentage of metal elements, ranging from 45≤a≤55, 36≤b≤43, 3≤c≤6, 3.5≤d≤7.5, 1.5≤e≤3. Titanium alloys exhibit an initial microstructure characterized by an equiaxed ultrafine grain (UFG) structure, which is strengthened by the hierarchical nanostructure formed during the subsequent deformation process.
[0041] Preferably, the titanium alloy contains 48 atomic % Ti, 39 atomic % Zr, 4.5 atomic % Hf, 6.3 atomic % Nb and 2.2 atomic % Sn.
[0042] The invention is characterized in that the ultrafine grain structure is capable of undergoing a reversible transformation induced plasticity (TRIP) effect and is enhanced during deformation by a hierarchical nanostructure. The hierarchical nanostructure may be nanotwinned, and one or more nanoribbons are confined within the nanotwinned. In addition, the alloy provides additional advantages due to its competitive corrosion resistance, coupled with the fact that the alloy composition is carefully selected from non-toxic elements.
[0043] In another embodiment, the TRIP effect and other subsequent strengthening mechanisms should be able to occur within the UFG structure.
[0044] In one embodiment, the average size of the UFG structure is 300 nanometers to 2 micrometers. When the annealing time is in the range of 25 to 45 seconds, the UFG structure has an average size of 400 nanometers. When the annealing time is in the range of 45 to 75 seconds, the average size of the UFG structure is 1.7 micrometers.
[0045] Since the alloy is strengthened by the reversible transformation induced plasticity (TRIP) effect in the early deformation stage, this makes the alloy exhibit pseudo-elasticity at lower deformation levels, allowing it to recover from about 5% strain and extend to about 7% at greater deformation. Specifically, the recoverable strain (RS) of the sample prepared in Example 1 reaches a maximum recoverable strain of about 7%. The RS of Sample 2 is about 5.6%. The RS of Sample 3 is about 4.3%.
[0046] In one embodiment, the alloy was subjected to more than one thousand fatigue cycles at a constant tensile stress of 1.4 GPa.
[0047] In one embodiment, the alloy contains non-toxic elements and exhibits corrosion resistance comparable to commercial TC4 alloy.
[0048] In another aspect, the present invention provides a method for preparing an ultra-tough multifunctional titanium alloy sheet, comprising weighing at least two raw materials with a purity higher than 95%, wherein the at least two raw materials include Ti, Zr, Hf, Nb and Sn; melting the at least two raw materials by arc melting in a pure argon atmosphere to obtain a molten alloy; casting the molten alloy into a water-cooled copper mold; cold rolling the cast alloy to reduce its thickness by 97%-99% to obtain a cold-rolled alloy sheet; wrapping the cold-rolled alloy sheet in an iron sheet, annealing at 800°C to 900°C for a period of time in a continuously flowing argon atmosphere, and then air cooling to obtain a titanium alloy sheet.
[0049] In one embodiment, the step of melting the at least two raw materials by arc melting under pure argon atmosphere to obtain a molten alloy comprises a series of melting and remelting processes, for a total of 7-8 cycles.
[0050] In one embodiment, the annealing time is between 20 seconds and 20 minutes. When the annealing time is in the range of 25 to 45 seconds, the titanium alloy exhibits a tensile strength of about 1.75 GPa while having a uniform elongation of at least 20%.
[0051] In another embodiment, when the annealing time is in the range of 45 to 75 seconds, the titanium alloy exhibits a tensile strength of about 1.5 GPa, while having a uniform elongation of at least 15%. For example, the titanium alloy exhibits a tensile strength of about 1.5 GPa, plus a uniform elongation of 18%.
[0052] In yet another embodiment, when the annealing time is in the range of 12 to 20 minutes, the titanium alloy exhibits a tensile strength of about 1.2 GPa and a uniform elongation of at least 17%. For example, the titanium alloy has a tensile strength of about 1.2 GPa and a uniform elongation of 17.3%.
[0053] The following examples illustrate the present invention but are not intended to limit the present invention.
[0054] Example
[0055] Example 1 - Preparation of TiZrHfNbSn alloy
[0056] In this example, the designed β-Ti alloy (called TiZrHfNbSn) has the composition specified in Table 1 and is prepared by arc melting under pure argon atmosphere using high purity raw materials. To ensure chemical homogeneity, the alloy undergoes a series of melting and remelting processes, a total of 7-8 cycles, and then is cast in a water-cooled copper mold with a cross-sectional area of 10×10 square meters. The cast alloy is cold rolled until the thickness reduction reaches about 99% without any intermediate annealing step. The cold rolled alloy sheet is then wrapped in iron sheets, annealed at 800°C for recrystallization, and then air cooled. A flowing argon atmosphere is provided to prevent oxidation during annealing.
[0057] Table 1 - Nominal composition of TiZrHfNbSn alloy
[0058] The initial microstructure is highly sensitive to the annealing time, which has a significant impact on the mechanical and functional properties. In this example, three different samples (Sample 1, Sample 2, and Sample 3) were prepared based on different annealing times. For Samples 1 to 3, the annealing time was set to 30 seconds, 45 seconds, and 15 minutes, respectively.
[0059] In sample 1, the annealing time was 25-45 seconds, and the sample exhibited an average grain size of about 400 nm. The ultimate tensile strength (UTS), uniform elongation (UE), and recoverable strain (RS) of sample 1 were 1.75 GPa, 20%, and 7.0%, respectively.
[0060] In sample 2, the annealing time is 45-75 seconds, and the average grain size of the sample is about 1.7 microns. The UTS, UE and RS of sample 2 are 1.55 GPa, 18% and 5.6% respectively.
[0061] In sample 3, the annealing time is 12-20 minutes, and the average grain size of the sample is about 31 microns. The UTS, UE and RS of sample 3 are 1.20 GPa, 17.3% and 4.3%, respectively.
[0062] Example 2 - Microstructural Characterization of TiZrHfNbSn Alloy
[0063] Its microstructure was characterized using electron backscatter diffraction (EBSD) and transmission electron microscopy (TEM). The basic principle of EBSD is that when an electron beam hits the surface of a material, the scattered electrons will have a specific energy and direction distribution, which depends on the crystal structure and lattice orientation of the material. By detecting these backscattered electrons, crystallographic information about the material can be obtained. The EBSD technique is used to collect and analyze diffraction patterns to infer properties such as crystal orientation, grain boundary distribution, grain size, and crystal deformation.
[0064] The alloy pieces used for EBSD testing were electropolished until the surface became mirror-bright. The electropolishing solution was HNO3: methanol (1:4), where the voltage was set to 25V and the temperature was kept below -40°C. EBSD testing was performed by a FEI Scios scanning electron microscope equipped with an EDAX Velocity camera at an accelerating voltage of 20kV and a current of 13nA.
[0065] The TEM samples were initially prepared by mechanical grinding and polishing to a thickness of approximately 30 μm. Subsequently, disks with a diameter of 3 mm (Φ3 mm) were extracted from the sheets and further thinned by a precision ion polishing system (PIPS II, model 695, Gatan) until an electron-transparent thickness was reached. The thinning temperature was maintained at −100 °C to preserve metastable or deformed microstructures. TEM analysis was performed using a JEOL-2100F transmission electron microscope operated at 200 kV.
[0066] refer to Figure 1A-1B The initial microstructure of sample 1 tested by EBSD and TEM showed the formation of a uniform equiaxed ultrafine grain (UFG) structure, with an average size of 400 ± 160 nm as determined by statistical analysis of EBSD data. The microstructure consisted of a single β phase, and the recrystallization process was fully completed, with almost no dislocations observed in the TEM bright field (BF) image ( Figure 1B ).
[0067] Go to Figure 2A-2B , it is clear that the grain size increases proportionally with the duration of annealing. Although the equiaxed grain structure is retained in Sample 2, the average grain size increases from about 400 nanometers to about 1.7 micrometers.
[0068] Go to Figure 3 , the same trend is observed in sample 3 as the annealing time continues to increase. The average grain size increases to 31 μm and the fine grain structure no longer exists.
[0069] Example 3 - Mechanical Properties and Functional Properties of TiZrHfNbSn Alloy
[0070] Flat dog-bone tensile specimens with dimensions of 12.5 × 3.2 × 0.1 cubic meters were cut from the alloy plates using a ProtoMAX abrasive water jet cutter. Tensile tests were performed at room temperature on an Instron 3382 series universal testing machine. For mechanical property testing, the specimens were tested at 0.001 s -1 The strain rate is 0.001s -1Functional properties were tested by cyclic loading-unloading-reloading (LUR) tests at a strain rate of 1.5 s / min, where the strain was increased by 1% in each cycle until it reached 8%. In addition, separate tensile tests were performed with different pre-strains from 1% to 10%. Fatigue tests were performed at 0.002 s / min. -2 The LUR test was performed at a strain rate of 1.4 GPa with a constant applied stress of 1.4 GPa.
[0071] Steering Figure 4A The stress-strain curve of sample 1 shows a characteristic two-step yielding behavior associated with the TRIP effect. The first yield is the induced β→α” martensitic phase transformation (σM), and the second yield is associated with the common dislocation slip (σy). It can be observed that sample 1 exhibits a high σM of about 1.36 GPa and an ultimate tensile strength (UTS) of about 1.75 GPa, as well as a uniform elongation (UE) higher than 20%.
[0072] Steering Figure 4B As the annealing time increases, the σM, UTS and UE of sample 2 decrease to 1.06 GPa, 1.55 GPa and 18%, respectively. As the annealing time continues to increase, the σM, UTS and UE of sample 3 further decrease to 0.63 GPa, 1.20 GPa and 17.3%, respectively. Figure 4C ).
[0073] Since sample 1 exhibits superior mechanical properties compared to the other two samples, its microstructure during deformation is of great interest and thus a thorough investigation was performed to deeply investigate the underlying mechanism.
[0074] Figure 5 The true stress-strain curve and the corresponding strain hardening rate are shown for sample 1. The strain hardening rate reaches a maximum value at a true strain of about 10% and then remains at a relatively high and stable value until fracture.
[0075] TEM characterization was performed at 10%, 15% strain and fracture conditions to study the evolution of the microstructure. The study started with 10% strain because the initial stage of the enhanced plastic behavior is reversible. "Martensitic transformation is considered. Insufficient deformation below 10% will not be able to fully stabilize the α" phase through dislocation activity.
[0076] Figures 6A-6H The microstructural evolution at different strain stages (no strain, 10%, 15%, and fracture) is shown. Before deformation, the alloy exhibits a single β phase with an initial equiaxed ultrafine grain (UFG) structure. When the sample is deformed to 10%, multiple α″ laths are observed in the βUFG. The remaining β phase is associated with the reverse martensitic transformation upon unloading ( Figure 6B). When further deformed to 15%, the β phase almost no longer exists. The microstructure at this time is all α” nanotwins, which are stabilized by severe plastic deformation and confined in UFG ( Figure 6C ). In addition, nanoribbon-like structures were observed to be encapsulated in each α” nanotwin. These structures are believed to help disperse stress concentration throughout the UFG and nanotwins. These nanoribbons are believed to be the result of late deformation as they were not observed at 10% strain ( Figure 6B Finally, these hierarchical nanostructures persist until the deformed sample reaches fracture ( Fig.6D ).
[0077] The present invention further investigates nanoribbons confined within a single α” twin. Although the nanoribbons exhibit different contrasts ( Fig. 6E ), but HRTEM and fast Fourier transform (FFT) analysis showed that their interface relationship is not twinning ( Figure 6F-6H ).
[0078] Example 4 - TiZrHfNbSn alloy Pseudo Elasticity and fatigue properties
[0079] Since the plastic behavior of TiZrHfNbSn alloy is enhanced by the reversible TRIP effect in the early stage of deformation, pseudoelasticity is expected to be obtained in the samples in addition to the true elasticity upon unloading. Therefore, cyclic tensile tests were performed on samples 1–3.
[0080] Figure 7 The LUR curves during the tensile cycle test are shown. The results show that the shape recovery rate decreases with increasing grain size. When the strain reaches 8%, sample 1 exhibits a recoverable strain of about 6.5%, while samples 2 and 3 show values of about 5.6% and 4.3%, respectively. It is possible that the UFG structure in sample 1 suppresses dislocation motion, thereby improving the stability of the sample.
[0081] refer to Fig. 8A To evaluate the pseudoelastic capacity of sample 1, separate tensile tests were performed at different pre-strains from 1% to 10%. The sample recovered almost completely from a deformation of 4%-5%. When the deformation exceeded 8%, the maximum recoverable strain reached about 7%.
[0082] To test the functional stability, the samples were subjected to tensile fatigue tests at a constant applied stress of 1.4 GPa ( Figure 8B The deformation curve reaches a stable state after about 100 cycles ( Figure 8C). This stability continued until the fatigue cycles exceeded 1300 and the sample broke. This combination of ultra-high stress and pseudo-elasticity, coupled with stable fatigue performance, means that the sample has the potential to be used as an advanced damping material for extreme conditions.
[0083] Example 5 - Electrochemical Corrosion Performance of TiZrHfNbSn Alloy
[0084] The as-cast alloy was cold rolled to obtain an appropriate thickness of 0.8 mm to 1.0 mm. Subsequently, the sample was recrystallized at 800°C for one minute. Cylinders with a diameter of Φ12 mm were then cut from the alloy plate using a ProtoMAX abrasive water jet cutting machine.
[0085] The surface of the cylinder to be subjected to electrochemical testing was mechanically ground and polished to ensure surface roughness. For comparison, a commercial TC4 alloy was provided and subjected to the same pretreatment. The electrochemical tests were carried out in simulated body fluid (SBF) solution using CHI 760E at a temperature of 37°C and pH 7.4. The electrochemical cell was a standard three-electrode device equipped with a platinum sheet as the counter electrode (CE), a saturated calomel electrode as the reference electrode (SCE), and an alloy as the working electrode (WE). The exposed area of WE was 1 square meter. Before the test, WE was immersed in SBF for 2 hours to reach a steady state of open circuit potential (OCP).
[0086] Reference Fig. 9 , showing the anodic dissolution and passivation behavior of TiZrHfNbSn alloy and commercial TC4 alloy in SBF solution. In general, excellent corrosion resistance is associated with lower corrosion density (I corr ), higher corrosion potential (E corr ) and pitting potential (E pit ). In the present invention, the potentiodynamic polarization curves of the alloys do not show significant differences. Compared with the TC4 alloy, the TiZrHfNbSn alloy shows a slightly lower I cor In contrast, the TC4 alloy exhibits a slightly higher E corr and E pit This indicates that the corrosion resistance of TiZrHfNbSn is comparable to that of TC4 alloy. The detailed electrochemical results are shown in Table 2. In addition, all constituent elements in TiZrHfNbSn are non-toxic, which gives the alloy an advantage in biocompatibility.
[0087] Table 2 - Electrochemical parameters of the alloys in SBF solution at 37 °C
[0088] In summary, the present invention has developed a metastable titanium alloy capable of multifunctional use. The initial microstructure is characterized by an equiaxed UFG structure, which is further enhanced by a hierarchical nanostructure during deformation. The alloy of the present invention has ultra-high strength and pseudo-elasticity, indicating its ability to absorb high energy. The alloy exhibits continuous strain hardening, with a high tensile strength of about 1.75 GPa and a ductility of more than 20%. In the early stages of deformation, due to the enhancement of the reversible transformation induced plasticity (TRIP) effect, the alloy exhibits pseudo-elasticity at lower deformation levels, with a maximum recoverable strain of 7%. Regarding biocompatibility, the alloy shows electrochemical corrosion resistance comparable to that of Ti-6Al-4V in a simulated body fluid (SBF) environment.
[0089] Combined with its resistance to high stress fatigue testing, the alloy is expected to be used as advanced damping devices and shock absorbers in the aerospace or automotive industries. In biomedical applications, the alloy can be used as stent grafts, orthodontic and orthopedic implants. Due to the absence of toxic elements and competitive corrosion resistance, the alloy may become a strong competitor to commercial biomedical TC4 and Ti-Ni alloys.
[0090] Industrial Applicability:
[0091] The invention has potential applications in the biomedical, aerospace and automotive fields. In biomedical applications, it can be used as a safer and more biocompatible bioimplant compared to existing titanium alloy implants. Therefore, the alloy may become a strong competitor to commercial biomedical β-Ti alloys and Ti-Ni SMA.
[0092] For aerospace and automotive applications, its ultra-high strength, pseudo-elasticity and fatigue resistance properties enable it to be used as a damping device, shock absorber and vibration absorber. Therefore, it can be used as a new and advanced functional material in areas with challenging and demanding conditions.
[0093] definition
[0094] Throughout the specification, unless otherwise specified, the term "comprise" or variations such as "include" or "contain" will be understood to include a specified integer or integers, but not to exclude the inclusion of any other integers or groups of integers. It should also be noted that in this disclosure, especially in the claims or during, or the terms "comprise" or "include" or "contain" have the meanings given to it in the U.S. patent law. For example, they allow for undefined elements of the description, but exclude elements found in the prior art or affecting the basic or novel characteristics of the invention.
[0095] Furthermore, throughout the specification and claims, unless required otherwise, the term "comprise" or variations thereof, will be understood to imply the inclusion of a stated integer or group of integers but not the exclusion of any other integers or groups of integers.
[0096] When the description refers to "one embodiment", "embodiment", "example embodiment" and the like, it means that the described embodiment may include specific features, structures or characteristics, but each embodiment may not necessarily include specific features, and these features do not necessarily refer to the same embodiment. In addition, when a specific feature, structure or characteristic is described in conjunction with an embodiment, it is considered that it is within the knowledge of those skilled in the art, and these features, structures or characteristics can be combined with other embodiments to function, whether or not explicitly described.
[0097] As used herein, the terms "substantially," "essentially," "approximately," and "about" are used to describe and explain a small change. When used in conjunction with an event or circumstance, the terms may refer to the situation where the event or circumstance occurs exactly, as well as the situation where the event or circumstance occurs approximately. For example, when used in conjunction with a numerical value, these terms may include a range of variation less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%.
[0098] In the preparation methods described herein, the steps may be performed in any order without departing from the principles of the invention unless a time sequence or an operational order is explicitly described. In a claim, it should be stated that one step is performed first and then several other steps are performed, which means that the first step is performed before any other steps, but the other steps may be performed in any appropriate order unless the sequence is further listed in the other steps. For example, a claim element listing "step A, step B, step C, step D, and step E" should be understood as step A being performed first and step E being performed last, and steps B, C, and D may be performed in any order between steps A and E, and the order is still within the literal scope of the claim process. A given step or subset of steps may also be repeated.
[0099] The TRIP effect refers to a phenomenon in materials science whereby the deformation and mechanical properties of a material change due to a phase change that occurs during plastic deformation. In the context of alloys, such as certain steels, when they undergo plastic deformation, a phase change from one crystal structure to another can occur, resulting in improved ductility, strain hardening, and energy absorption.
[0100] "TC4" refers to a type of titanium alloy, commonly known as Ti-6Al-4V alloy. This alloy is a combination of titanium and aluminum, containing 6% aluminum and 4% vanadium. It has high strength and excellent corrosion resistance and is often used in aerospace and medical device applications.
[0101] Other definitions of selected terms used herein may be considered within the specific embodiments of the present invention and are applied throughout the specific embodiments of the present invention. Unless otherwise defined, all other technical terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs.
[0102] Those skilled in the art will appreciate that, in light of these teachings, alternative embodiments may be implemented without undue experimentation or departure from the spirit or scope of the invention as set forth in the appended claims. The present invention is limited solely by the appended claims, which encompass all such embodiments and modifications when viewed in conjunction with the above description and drawings.
[0103] References: The disclosures of the following references are incorporated by reference [1] Veiga C, Davim JP, Loureiro AJ R., Properties and applications of titanium alloys: a brief review [J]. Rev. Adv. Mater. Sci, 2012, 32(2): 133-148. [2] Niinomi M., Mechanical properties of biomedical titanium alloys [J]. Materials Science and Engineering: A, 1998, 243(1-2): 231-236. [3] Otsuka K, Ren X., Recent developments in the research of shape memory alloys[J]. Intermetallics, 1999, 7(5): 511-528. [4] Kim HY, Ikehara Y, Kim JI et al., Martensitic transformation, shape memory effect and superelasticity of Ti-Nb binary alloys [J]. Acta Materialia, 2006, 54(9): 2419-2429. [5] Gupta RK, Kumar VA, Mathew C, et al., Strain hardening of titanium alloy Ti6Al4V sheets with prior heattreatment and cold working [J]. Materials Science and Engineering: A, 2016, 662: 537-550. [6]Marteleur M, Sun F, Gloriant T et al., On the design of new β-metastable titanium alloys with improved work hardening rate thanks to simultaneous TRIP and TWIP effects [J]. Scripta Materialia, 2012, 66(10): 749-752. [7] Dumas O, Malet L, P et al., Reorientation Induced Plasticity (RIP) in high-strength titanium alloys: An insight into the underlying mechanisms and resulting mechanical properties [J]. Acta Materialia, 2023, 246: 118679. [8] Biesiekierski A, Wang J, Gepreel MAH et al., A new look at biomedical Ti-based shape memory alloys [J]. Actabiomaterialia, 2012, 8(5): 1661-1669. [9] Niinomi M, Nakai M, Hieda J et al., A review of surface modification of a novel low modulus β-type titanium alloy for biomedical applications [J]. International Journal of Surface Science and Engineering 15, 2014, 8(2-3): 138-152.
Claims
1. An ultra-tough multifunctional titanium alloy made of two or more metal elements, characterized in that: The molecular formula of the titanium alloy is Ti a Zr b Hf c Nb d Sn e , a, b, c, d and e represent the atomic percentage of metal elements, ranging from 45≤a≤55, 36≤b≤43, 3≤c≤6, 3.5≤d≤7.5, 1.5≤e≤3, and the titanium alloy presents an initial microstructure characterized by an equiaxed ultrafine grain (UFG) structure, wherein the UFG structure is enhanced by a hierarchical nanostructure formed during subsequent deformation.
2. The super-tough multifunctional titanium alloy according to claim 1, wherein the titanium alloy comprises 48 atomic % Ti, 39 atomic % Zr, 4.5 atomic % Hf, 6.3 atomic % Nb and 2.2 atomic % Sn.
3. The ultra-tough multifunctional titanium alloy according to claim 1, wherein the hierarchical nanostructure comprises nanotwins, and wherein one or more nanoribbons are confined within the nanotwins.
4. The ultra-tough multifunctional titanium alloy according to claim 1, wherein the average size of the UFG structure is 300 nanometers to 2 micrometers.
5. The ultra-tough multifunctional titanium alloy according to claim 1, wherein the titanium alloy exhibits a tensile strength of about 1.75 GPa and a uniform elongation of at least 20%.
6. The ultra-tough multifunctional titanium alloy according to claim 1, wherein the titanium alloy withstands more than 1000 fatigue cycles under a constant tensile stress of 1.4 GPa.
7. The ultra-tough multifunctional titanium alloy according to claim 1, wherein the titanium alloy exhibits almost complete deformation recovery within a deformation range of 4% to 5%.
8. The ultra-tough multifunctional titanium alloy according to claim 1, wherein the titanium alloy achieves a maximum recoverable strain of about 7%.
9. A method for preparing a super-tough multifunctional titanium alloy sheet, comprising the following steps: Weighing at least two raw materials with a purity higher than 95%, wherein the at least two raw materials include Ti, Zr, Hf, Nb and Sn; melting the at least two raw materials by arc melting under a pure argon atmosphere to obtain a molten alloy; pouring the molten alloy into a water-cooled copper mold; Cold rolling the cast alloy to reduce the thickness by 97%-99%, thereby obtaining a cold-rolled alloy sheet; The cold rolled alloy sheet is wrapped in an iron sheet, annealed at 800° C. to 900° C. for a period of time in a continuously flowing argon atmosphere, and then air-cooled to obtain a titanium alloy sheet.
10. The method according to claim 9, wherein the titanium alloy containing the at least two raw materials has a molecular formula Ti a Zr b Hf c Nb d Sn e , wherein a, b, c, d and e represent the atomic percentage of the metal element, ranging from 45≤a≤55, 36≤b≤43, 3≤c≤6, 3.5≤d≤7.5, 1.5≤e≤3.
11. The method according to claim 9, wherein the step of melting the at least two raw materials by arc melting under pure argon atmosphere to obtain a molten alloy comprises a series of melting and remelting processes, a total of 7-8 cycles.
12. The method according to claim 9, wherein the annealing time is 20 seconds to 20 minutes.
13. The method of claim 12, wherein the titanium alloy has a tensile strength of about 1.75 GPa and a uniform elongation of at least 20% when the annealing time is in the range of 25 to 45 seconds.
14. The method of claim 12, wherein the titanium alloy exhibits a tensile strength of about 1.5 GPa and a uniform elongation of at least 15% when the annealing time is in the range of 45 to 75 seconds.
15. The method of claim 12, wherein the titanium alloy exhibits a tensile strength of about 1.2 GPa and a uniform elongation of at least 17% when the annealing time is in the range of 12 to 20 minutes.